Adhesive and tough hydrogels promoted by quaternary chitosan for strain sensor. (15th February 2021) - Wang, Te; Ren, Xiuyan; Bai, Yu; Liu, Li; Wu, Guangfeng
Graphical abstract: Highlights: Hydrogels were prepared by adding HACC to the PAA/Fe 3+ cross-linking system. The hydrogel exhibited excellent self-healing and anti-swelling properties. The hydrogel could adhere to various materials through physical interactions. The hydrogel exhibited skin-like sensory capability for monitoring various human motions. The hydrogel had a performance similar to skin intelligence. Abstract: As a flexible material, hydrogels have attracted considerable attention in the exploration of various wearable sensor devices. However, the performance of the existing hydrogels is often too single, which limits its further application. Here, a conductive hydrogel with adhesiveness, toughness, self-healing and anti-swelling properties was successfully prepared by adding 2-hydroxypropyltrimethyl ammonium chloride chitosan (HACC) to the polyacrylic acid/ferric ionic (PAA/Fe 3+ ) cross-linking system. Based on the existence of three types of non-covalent interactions in the hydrogel system, including electrostatic interaction, coordination interaction and hydrogen bonds, the hydrogel possessed excellent mechanical properties (tensile stress and strain were 827 kPa and 1652 %, respectively), self-healing properties (self-healing efficiency reached 83.3 % at room temperature) and anti-swelling properties. In addition, the introduction of HACC also successfully gave the hydrogel outstanding adhesiveness. Moreover, the existence of iron ions provided sensitive conductivity to the hydrogel, which could be used as a flexible sensor for directly monitoring various motions. Therefore, this simple strategy for preparation of multifunctional hydrogels would expand the application of a new generation of hydrogel-based sensors.